2006
DOI: 10.1007/s00436-006-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Cornea as a tissue reservoir of Trypanosoma cruzi

Abstract: Trypanosoma cruzi causal agent of Chagas' disease is a paninfective parasite of mammals transmitted through skin fecal contamination by Triatominae vectors. Studies of alternative routes for infection are scarce; therefore, eye infection should be important, because of the eye's high blood irrigation and brain proximity, as port of entry of the parasite. Trypanosoma cruzi parasites and/or their genetic material in ocular and adjacent muscle tissues were studied in batches of six NMRI mice (15 g) and Trichomys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Using a mouse model, the possibility of the transfer of T. cruzi was determined in organs often used during these procedures. Isolates from D. marsupialis and R. rattus captured in Caracas were inoculated in adipose, bone-cartilage, and eye tissue, observing the intracellular presence of the parasite in all cases ( 39 – 41 ) (Figures 5 – 7 ). This constitutes an alternative transmission pathway, whereby natural T. cruzi intracellular multiplication could be enhanced in immunosuppressed hosts.…”
Section: Chronological Description Of Investigations Into the Chagas’mentioning
confidence: 99%
“…Using a mouse model, the possibility of the transfer of T. cruzi was determined in organs often used during these procedures. Isolates from D. marsupialis and R. rattus captured in Caracas were inoculated in adipose, bone-cartilage, and eye tissue, observing the intracellular presence of the parasite in all cases ( 39 – 41 ) (Figures 5 – 7 ). This constitutes an alternative transmission pathway, whereby natural T. cruzi intracellular multiplication could be enhanced in immunosuppressed hosts.…”
Section: Chronological Description Of Investigations Into the Chagas’mentioning
confidence: 99%
“…The UK Blood Transfusion and Tissue Transplantation Services, however, suggested that as there is no risk of transmitting T. cruzi because corneas are avascular. 117 Herrera et al 118 indicated that there few investigations of infection of the eye globe tissues by T. cruzi; however, their animal studies found T. cruzi in the ocular environment, which suggested the possible risk of transmission. The Canadian Blood Services has instituted a common policy to test for Chagas in blood donors in Canada and expects to implement similar policies for corneal tissue.…”
Section: Other Infectious Diseasesmentioning
confidence: 97%
“…Recently, the first case of Trypanosoma cruzi-associated retinitis was diagnosed [283]. The presence of T. cruzi amastigotes in the conjunctiva, corneal stroma, the adjacent ocular muscle, and the interstitial macrophages of Thrichomys apereoides (Rodentia, Echimyidae) experimentally infected with T. cruzi has been documented [284].…”
Section: Conjunctival Swab/lacrimal Fluid/occularmentioning
confidence: 99%